2016
DOI: 10.1038/srep26274
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD59 is a Novel Biomarker for the Prediction of Obstructive Chronic Lung Allograft Dysfunction After Lung Transplantation

Abstract: CD59 is a complement regulatory protein that inhibits membrane attack complex formation. A soluble form of CD59 (sCD59) is present in various body fluids and is associated with cellular damage after acute myocardial infarction. Lung transplantation (LTx) is the final treatment for end-stage lung diseases, however overall survival is hampered by chronic lung allograft dysfunction development, which presents itself obstructively as the bronchiolitis obliterans syndrome (BOS). We hypothesized that, due to cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
(45 reference statements)
1
25
0
Order By: Relevance
“…While no such validated biomarker currently exists in transplantation, there are complement-related candidates. Soluble CD59 (sCD59), which is associated with cellular damage, including post-myocardial infarction 68 , was found to be elevated in a cohort of patients who developed bronchiolitis obliterans syndrome (BOS) after lung transplantation 69 . Importantly, serum sCD59 concentrations were elevated prior to the clinical diagnosis of BOS in these patients, and sCD59 was determined to be an independent predictor for the development of BOS.…”
Section: Complement and Transplant Rejection Biomarkersmentioning
confidence: 99%
“…While no such validated biomarker currently exists in transplantation, there are complement-related candidates. Soluble CD59 (sCD59), which is associated with cellular damage, including post-myocardial infarction 68 , was found to be elevated in a cohort of patients who developed bronchiolitis obliterans syndrome (BOS) after lung transplantation 69 . Importantly, serum sCD59 concentrations were elevated prior to the clinical diagnosis of BOS in these patients, and sCD59 was determined to be an independent predictor for the development of BOS.…”
Section: Complement and Transplant Rejection Biomarkersmentioning
confidence: 99%
“…The validation cohort used in our study revealed the strength of these biomarkers for BOS prediction. They displayed similar performances to predict BOS according to their correlation of expression, with AUC values reaching 0.83, 0.77, and 0.78, respectively, and exceeding the performance of biomarkers already published ( 14 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 59%
“…CD59 can be released into the circulation or the interstitial fluid in a soluble form (sCD59) and can be detected in various body fluids including urine, milk, serum, and plasma. 22 25 Various studies have designated sCD59 as biomarker for disease activity. Elevated circulating sCD59 concentrations have been found in acute myocardial infarction, and higher serum titers of glycated sCD59 have been described in diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%